MODEL PELATIHAN GROOMING DAN SERVICE EXCELLENCE DI SMK NEGERI 5 NEGARA DESA PEKUTATAN JEMBRANA - I Ketut Sirna (Majalah Ilmiah Widyacakra, 2020)
AbstractGrooming, service excellence is one of the courses in the Hotel Marketing course offered in theManagement Study Program curriculum, Grooming, excellent service is very functioning as aservice company in hospitality services to maintain customer satisfaction. from this level at theSMK level there are still many student behavior that is still indifferent in behaving, as expectedby the Hospitality Industry World. So it is not uncommon that a hospitality company afterstudents are recruited so employees need time to be trained again in the form of grooming andservice excellence so that in dealing with guests can behave properly. As a lecturer I haveconducted training on grooming and service excellence at SMK Negeri 5 Negara, PekutatanVillage, Jembrana, with the results; Students have good Grooming, can actualize serviceexcellence, can master English Hospitality, and have good Character. And already has agrooming and service excellence handbook as the next training handle. So that later it can bepracticed in the community and the tourism industry in the region and elsewhere. Therebyincreasing economic growth in the area